Pengaruh Konsentrasi Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 8 Baubau - Nur Anifa; La Eru Ugi; Ernawati Jais (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2026)
The problem in this study is, is there any significant effect of learning concentration on mathematics learning outcomes of class VIII students of SMP Negeri 8 Baubau? The objective of this study is to find out yhe effect of learning concentration on mathematics learning outcomes of class VIII students of SMP Negeri 8 Baubau. This type of research is quantitative research with the Ex-Post Facto method, where the population of this study is all class VIII students of SMP Negeri 8 Baubau with a total of 104 students spread across 4 classes. While the sample in this study was 23 students. The instruments used were questionnaires about student learning concentration and documentation on monitoring student learning concentration while studying and mathematics learning outcomes of class VIII students of SMP Negeri 8 Baubau. This data was analyzed using descriptive analysis, inferential statistical analysis, and simple linear regression analysis. The result of this study concluded that there is a significant influence of learning concentration on the mathematics learning outcomes of class VIII students at SMP Negeri 8 Baubau.